Dysbiosis of the faecal microbiota in patients with Crohn's disease and their unaffected relatives - Joossens, Marie; Huys, Geert; Cnockaert, Margo; De Preter, Vicky; Verbeke, Kristin; Rutgeerts, Paul; Vandamme, Peter; Vermeire, Severine (Gut, 2011)
Background and aimsA general dysbiosis of the intestinal microbiota has been established in patients with Crohn's disease (CD), but a systematic characterisation of this dysbiosis is lacking. Therefore the composition of the predominant faecal microbiota of patients with CD was studied in comparison with the predominant composition in unaffected controls. Whether dysbiosis is present in relatives of patients CD was also examined.MethodsFocusing on families with at least three members affected with CD, faecal samples of 68 patients with CD, 84 of their unaffected relatives and 55 matched controls were subjected to community fingerprinting of the predominant microbiota using denaturing gradient gel electrophoresis (DGGE). To analyse the DGGE profiles, BioNumerics software and non-parametric statistical analyses (SPSS V.17.0) were used. Observed differences in the predominant microbiota were subsequently confirmed and quantified with real-time PCR.ResultsFive bacterial species characterised dysbiosis in CD, namely a decrease in Dialister invisus (p=0.04), an uncharacterised species of Clostridium cluster XIVa (p=0.03), Faecalibacterium prausnitzii (p<1.3×10−5) and Bifidobacterium adolescentis (p=5.4×10−6), and an increase in Ruminococcus gnavus (p=2.1×10−7). Unaffected relatives of patients with CD had less Collinsella aerofaciens (p=0.004) and a member of the Escherichia coli–Shigella group (p=0.01) and more Ruminococcus torques (p=0.02) in their predominant microbiota as compared with healthy subjects.ConclusionUnaffected relatives of patients with CD have a different composition of their microbiota compared with healthy controls. This dysbiosis is not characterised by lack of butyrate producing-bacteria as observed in CD but suggests a role for microorganisms with mucin degradation capacity.